Quantum dot composite microsphere and method prepared by atomic layer deposition and atomic layer etching

By using ALD and ALE technologies to coat semiconductor thin films layer by layer on quantum dot core materials, the problems of inaccurate quantum dot size regulation and easy agglomeration in the prior art are solved, and efficient and accurate quantum dot preparation is achieved, with wide applicability.

CN118562491BActive Publication Date: 2025-03-11BATTFLEX (WUHAN) TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410737808.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-07
Publication Date
2025-03-11
Estimated Expiration
2044-06-07

AI Technical Summary

Technical Problem

Existing quantum dot preparation technology cannot achieve Ametre-level precision regulation, which can easily lead to quantum dot agglomeration and has limited applicability.

Method used

Atomic layer deposition (ALD) and atomic layer etching (ALE) technology are used to coat different types of semiconductor thin films layer by layer on non-semiconductor metal oxides or semiconductor metal oxide core materials to achieve precise control of quantum dot size and film thickness.

Benefits of technology

Aemite-level precision regulation of quantum dot size is achieved, which avoids agglomeration, improves efficiency, and has broad applicability, meeting the needs of high efficiency and diversified quantum dots.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118562491B_ABST
    Figure CN118562491B_ABST
Patent Text Reader

Abstract

The present invention provides a quantum dot composite microsphere and method prepared by atomic layer deposition and atomic layer etching, including using atomic layer deposition to coat a semiconductor film on the outside of a core material to a thickness of more than 21nm, and using atomic layer etching to etch the semiconductor film to a thickness of no more than 5nm, wherein the core material is a non-semiconductor metal oxide or silicon dioxide. The present invention uses atomic layer deposition (ALD) combined with atomic layer etching (ALE) technology to achieve angstrom-level precision control of the size of quantum dots, effectively solving the problem that this precision cannot be achieved in the prior art, thereby improving the performance and application range of quantum dots; at the same time, it avoids the easy agglomeration of quantum dots during the preparation process, improves the efficiency of quantum dots, and forms a uniform, dense, and thickness-controllable quantum dot film; different types of quantum dot films can be deposited, with a wide range of applicability, meeting the market demand for diversified quantum dots.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention mainly relates to the technical fields of atomic layer deposition, atomic layer etching and quantum dot particle preparation. Background Art

[0002] Quantum dots are nanoscale semiconductor materials that are widely used in solar cells, LED displays, and biomedical imaging due to their unique optical and electronic properties. The performance of quantum dots is closely related to their size and chemical composition. By changing these parameters, their emission spectrum can be adjusted to cover the entire visible light region. However, the preparation process of quantum dots is complicated, and due to their high surface energy, they are prone to agglomeration, which will reduce their efficiency.

[0003] Atomic layer deposition (ALD) and atomic layer etching (ALE) are two advanced semiconductor process technologies that can precisely control the thickness and composition of thin films at the nanometer level. ALD technology deposits thin films layer by layer on the substrate by alternately introducing different gas precursors, while ALE technology achieves precise control of film thickness by selectively removing part of the film.

[0004] Existing quantum dot preparation technologies mainly include colloidal synthesis, organometallic chemical vapor deposition, and molecular beam epitaxy. These methods can control the emission spectrum of quantum dots by changing their size and chemical composition. However, these methods usually cannot achieve angstrom-level precision control of quantum dot size and are prone to cause quantum dot agglomeration. As proposed in the prior art CN117467427A, a quantum dot composite microsphere, a quantum dot composite microsphere film and a preparation method thereof, the prepared quantum dot microsphere has a diameter of 60-400nm, wherein the inner core diameter is 30-150nm, the quantum dot diameter of the quantum dot layer is 10-20nm, and the outer shell thickness is 10-50nm. The quantum dots are single-structure quantum dots and core-shell structure quantum dots, and the types of quantum dots are different. In order to achieve the purpose of expanding the spectral range, the diameter of the quantum dot microsphere, the size of the quantum dots and the thickness of the outer shell are crucial. If the diameter of the quantum dot composite microsphere is too large, the thickness of the prepared quantum dot composite microsphere film will be too large. If the diameter of the quantum dot composite microsphere is too small, the performance of the prepared quantum dot composite microsphere film will be unstable and the quantum dots will easily agglomerate. If the size of the shell layer is too large, that is, the proportion of the shell layer is too large, resulting in a low content of quantum dots in the quantum dot composite microspheres. If the size of the shell layer is too small, the quantum dots in different quantum dot composite microspheres will be too close to each other, resulting in the light emitted by the quantum dots in the quantum dot composite microspheres being absorbed by the quantum dots in other quantum dot composite microspheres, and the luminescence efficiency of the prepared quantum dot composite microsphere film will be reduced.

[0005] The existing method of preparing three or more multi-component composite quantum dots generally involves first preparing the cores of different quantum dots and then coating the cores with metal sulfides. However, the size, morphology and optical properties of quantum dots are significantly affected by the synthesis conditions (such as temperature, concentration, pH value, etc.). When the thickness of the sulfide is thick, it is difficult to form a quantum effect. Therefore, it is a challenge to accurately control the synthesis process to obtain quantum dots with the desired performance. Although the ZnS shell can improve the chemical stability of quantum dots, it may still degrade or agglomerate under certain extreme conditions (such as strong acid and strong base environments), affecting its performance and application. Summary of the invention

[0006] There are several major problems in the existing quantum dot preparation technology: First, it is impossible to achieve angstrom-level precision control of the quantum dot size, which will affect the performance and application range of the quantum dots; second, quantum dots are prone to agglomeration during the preparation process, which will reduce their efficiency; third, the existing preparation technology is often only applicable to specific types of quantum dots and lacks wide applicability. In addition, although the existing atomic layer deposition and atomic layer etching technologies can accurately control the thickness and composition of the film at the nanometer level, their application in quantum dot preparation is relatively small. This technical solution mainly adopts the following technical solutions:

[0007] The present invention provides a quantum dot with a non-semiconductor metal oxide or silicon dioxide as a core material, and proposes a corresponding preparation method, the specific steps of which are as follows:

[0008] S01. Using atomic layer deposition to coat the core material with a semiconductor film;

[0009] S02. Etching the semiconductor film coated in step S01 to a thickness of no more than 5 nm by atomic layer etching;

[0010] S03 repeats steps S01~S02, successively coating multiple layers of different types of semiconductor films on the outside of the core material;

[0011] The core material is a non-semiconductor metal oxide, and the metal in the metal oxide includes silicon.

[0012] The present invention also provides a quantum dot with a semiconductor metal oxide as a core material, and proposes a corresponding preparation method, the specific steps of which are as follows:

[0013] T01. Atomic layer etching is used to etch a core material having a diameter of not less than 50 nm to a diameter of not more than 10 nm, wherein the core material is a semiconductor nanoparticle.

[0014] After step T01, the following steps are also included:

[0015] T02. Atomic layer deposition is used to coat the core material with a semiconductor film, and the material of the semiconductor film is different from that of the core material;

[0016] T03. The semiconductor film coated in step T02 is etched to a thickness of no more than 5 nm by atomic layer etching;

[0017] Step T03 also includes step T04: repeating steps T02 to T03, and sequentially coating the core material with multiple layers of semiconductor films of different types.

[0018] The diameter of the core material is 50-100 nm.

[0019] In the above method, the atomic layer deposition method includes: placing the material to be coated in a reaction chamber; providing source gas and reaction gas to grow a semiconductor film on the material to be coated.

[0020] In the above method, the semiconductor film includes II-VI semiconductors, III-V semiconductors, IV-VI semiconductors and multinary metal chalcogenides;

[0021] The source gas and the reaction gas include at least one of an organic complex containing a IIB subgroup element and a halide, and any one of a hydride containing a VI main group element and a single gas that can react with each other to deposit a II-VI semiconductor on the surface of the material to be coated;

[0022] The source gas and the reaction gas include at least one of an organic complex containing a IIIA subgroup element and a halide, and any one of a hydride containing a V main group element and an organic complex gas, which can react with each other to deposit a III-V semiconductor on the surface of the material to be coated;

[0023] The source gas and the reaction gas include at least one of an organic complex containing an IVA main group element and a halide and any one of a hydride containing a VI main group element and an organic complex gas that can react with each other to deposit a IV-VI group semiconductor on the surface of the material to be coated;

[0024] The source gas and the reaction gas include at least one of an organic complex containing metal elements and a halide, and any one of a hydride and an organic complex gas containing a VI main group element, which can react with each other to deposit a multinary metal chalcogenide semiconductor on the surface of the material to be coated. The multinary metal chalcogenide semiconductor includes: binary metal chalcogenides and ternary metal chalcogenides.

[0025] In the above method, the atomic layer etching method comprises: exposing the semiconductor material to be etched to a surface treatment gas, and the surface treatment gas reacts with the surface of the semiconductor material to be etched to form a modified layer on the semiconductor material to be etched;

[0026] The semiconductor material to be etched on which the modified layer is formed is exposed to an etching gas, and the etching gas reacts with the modified layer to remove the modified layer on the semiconductor material to be etched.

[0027] Preferably, the surface treatment gas comprises a fluorine-based surface treatment gas, and the fluorine-based surface treatment gas comprises one or a combination selected from HF, NF3 and F2 gases;

[0028] The etching gas includes one or a combination of trimethylaluminum, trimethylamine (TMA), dimethylacetamide (DMAC), tetrachloride, Sn(acac)2, Al(CH3)2Cl, SiCl4, TiCl4, BCl3, and WF6.

[0029] Preferably, before exposing the semiconductor material to be etched to the surface treatment gas, the step is also included: exposing the semiconductor material to be etched to a gas containing oxygen ions to modify the surface of the semiconductor material to form a surface passivation layer, and the gas containing oxygen ions includes one of N2O, O2, and O3.

[0030] A quantum dot composite microsphere comprises a core material and at least one semiconductor film of a material different from the core material which is sequentially coated outside the core material, wherein the thickness of each semiconductor film layer is not greater than 5 nm, and the core material is a non-semiconductor metal oxide, wherein the metal in the metal oxide comprises silicon.

[0031] The core material is semiconductor nanoparticles with a diameter no greater than 10 nm.

[0032] The semiconductor film includes II-VI semiconductors, III-V semiconductors, IV-VI semiconductors and multinary metal chalcogenide semiconductors. The multinary metal chalcogenide semiconductors include binary metal chalcogenides and ternary metal chalcogenides.

[0033] The II-VI semiconductors include ZnO, ZnS, CdS, ZnSe, CdSe, HgSe, HgS, CdTe, ZnTe, HgTe, and CdSeTe.

[0034] The III-V semiconductors include GaN, InN, GaP, InP, and GaTe.

[0035] The IV-VI group semiconductors include PbS, PbSe, PbTe, GeS, GeSe, and SnS2.

[0036] The multinary metal chalcogenide semiconductor includes: binary metal chalcogenides and ternary metal chalcogenides. The metal in the binary metal chalcogenide includes one of Cu, Mn, Ni, Ag, Eu, Co, Pb, Ge, Sn, Bi, and Sb. The metal in the ternary metal chalcogenide includes one or two of Cd, Cu, In, Zn, Fe, Sn, Ge, Ag, Co, Cr, Bi, and Sb.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] 1) The present invention adopts atomic layer deposition (ALD) combined with atomic layer etching (ALE) technology, which can achieve angstrom-level precision control of quantum dot size and achieve uniform size control of quantum dot size, effectively solving the problem that the prior art (such as CN111662716B) cannot achieve uniform size control of quantum dots, so that the quantum dots prepared by the method of the present invention have consistent performance and application range.

[0039] 2) Using atomic layer etching technology, after forming a uniform and dense coating film, the quantum dot film is further thinned to the required thickness, achieving precise control of the thickness of the quantum dot film, avoiding agglomeration, improving the efficiency of the quantum dots, and meeting the market demand for high-efficiency quantum dots.

[0040] 3) Different types of quantum dot films can be deposited, which has wide applicability.

[0041] 4) The technical solution of the present invention can deposit different types of quantum dot films, has a wide range of applicability, and meets the market demand for diversified quantum dots. It effectively solves the problem in the prior art (such as CN111662716B) that the different reaction parameter control ranges lead to different reaction rates of quantum dot films, resulting in the emission wavelength shift of quantum dots.

[0042] Therefore, the quantum dots prepared by the method of the present invention all have a high fluorescence quantum yield, a stable emission wavelength range, and a stronger fluorescence intensity. Due to the advanced nature of the technical solution, it can be widely used in the fields of quantum dot preparation, optoelectronic device manufacturing, biomedical imaging, and solar cells. At the same time, with the development of science and technology, the application of quantum dots in various fields is becoming more and more extensive, and the demand for high-precision, high-efficiency, and widely applicable quantum dot preparation technology is also increasing. Therefore, the present invention has broad market prospects and application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 For ZnS at 300 o Schematic diagram of atomic layer epitaxy (ALE) rate under C. DETAILED DESCRIPTION

[0044] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0045] The embodiments of the present invention are provided to explain the present invention more completely to those skilled in the art. The following embodiments may be modified in various forms, and the scope of the present invention is not limited to the examples described below. On the contrary, these embodiments are provided to make the present disclosure thorough and complete and to fully convey the spirit of the present invention to those skilled in the art. In addition, for the convenience and clarity of explanation, the thickness or size of each layer in the drawings is exaggerated.

[0046] In order to enable those skilled in the art to clearly understand the implementation details and operations of the present invention, the above technical solutions are illustrated below by means of specific embodiments.

[0047] In this embodiment, a fluorescence spectrometer (Horiba Co., Japan, model Fluorolog-3-21, Tempro-01, using ultraviolet light with a wavelength of 365 nm as an excitation light source) was used to test the fluorescence spectra of the following quantum dots.

[0048] Example 1

[0049] (1) Preparation of quantum dot composite microspheres SiO2@ZnS:

[0050] a) preparing core material SiO2 particles with a diameter of 100 nm;

[0051] b) Atomic layer deposition technology is used to deposit a ZnS film on the surface of SiO2 particles, and the thickness of the ZnS film is 21nm;

[0052] The specific operation is to place SiO2 particles into the reaction chamber of the atomic layer deposition equipment (the SiO2 particles can be placed in a porous container with micropores, and the porous container can be rotated to make the SiO2 particles fully mixed in the porous container cavity. Or the SiO2 particles can be fluidized in the reaction chamber to achieve dispersion), and the reaction chamber is evacuated and the purge gas (nitrogen) is replaced at least three times to remove oxygen and water between the SiO2 particles or in the pores to prevent the residue from reacting with the source gas;

[0053] The working parameters of the atomic layer deposition equipment are as follows: the temperature is 200°C, the pressure is 1 Torr, the source gas (diethyl zinc) is carried into the reaction chamber by a purge gas, and adsorbed on the surface of the SiO2 particles until the pressure of the reaction chamber reaches 1 Torr and is maintained for 60 seconds, and then the remaining diethyl zinc and by-product acetylene are purged away by a purge gas, and the reaction gas (hydrogen sulfide) is carried into the reaction chamber by a purge gas until the pressure reaches 1 Torr and is maintained for 60 seconds, and reacts with the diethyl zinc that has been chemically adsorbed on the surface of the SiO2 particles to generate ZnS, and then the excess reaction gas and by-products are carried out of the reaction chamber by the purge gas, thus completing an ALD deposition cycle; the source gas (diethyl zinc), the purge gas and the reaction gas (hydrogen sulfide) are alternately pulsed into the reaction chamber;

[0054] In this step, the time of each pulse of source gas or reaction gas is 0.1 second, the interval between adjacent pulses is 5 seconds, and the exhaust gas in the reaction chamber is extracted at the same time as the pulse. The number of ALD deposition cycles is 100 times to ensure the uniformity and density of the ZnS film deposited on the surface of the SiO2 particles. Figure 1 As shown, the growth rate of the ZnS film is 0.21 nm per circle, and a ZnS film with a thickness of 21 nm is obtained.

[0055] c) Atomic layer etching technology is used to thin the ZnS film to less than 5nm.

[0056] The specific operation is to put SiO2 particles deposited with ZnS film into the reaction chamber of the atomic layer etching equipment, set the working parameters of the equipment, such as temperature of 200°C and pressure of 0.5 Torr, use purge gas to carry surface treatment gas (hydrogen fluoride) pulse into the reaction chamber to fluorinate ZnS to form ZnF3, until the pressure of the reaction chamber reaches 0.5 Torr and is maintained for 60 seconds, then use purge gas to purge away the remaining surface treatment gas and by-product hydrogen sulfide, and also use purge gas to carry etching gas (trimethylaluminum) pulse into the reaction chamber until the pressure reaches 0.5 torr and is maintained for 60 seconds, which is used to corrode ZnF3 to form Zn(CH3)2 and AlF(CH3)2, and then the excess etching gas and by-products are taken out of the reaction chamber by the purge gas, thus completing an ALE etching cycle;

[0057] Hydrogen fluoride and trimethylaluminum are pulsed into the reaction chamber alternately. The time of each pulse of surface treatment gas or etching gas is 0.05 seconds, and the interval between adjacent pulses is 2 seconds. The tail gas in the reaction chamber is extracted at the same time of the pulse. The ALE etching cycle is 150 times, and the etching speed is 0.1 nanometers per circle. The thickness of the ZnS film is precisely thinned to less than 5 nanometers. In this way, the size of ZnS quantum dots can be precisely controlled at the angstrom level to avoid agglomeration and improve its efficiency.

[0058] In step b) of this embodiment, when ZnS is deposited on the surface of SiO2 particles, only ZnS nanoparticles are formed in the first 10 deposition cycles, and then a ZnS film is formed as the number of deposition cycles increases, but the thickness exceeds 20 nm.

[0059] In step c) of this embodiment, before each etching step is performed by alternately introducing the surface treatment gas (HF) and the etching gas (trimethylaluminum), the semiconductor layer deposited by atomic layer deposition is modified by using a purge gas carrying a gas containing oxygen ions to form a surface passivation layer. The gas containing oxygen ions includes one of N2O, O2, and O3. Since the surface of the III-V or II-VI group compound is modified by oxygen ions, a high-density passivation layer is formed, so that the etching depth achieved each time the ALE cycle is performed can be controlled at the single-atom level. The reaction of forming the passivation layer in the above technical solution is self-limiting, so that the etching depth of ALE can be accurately controlled.

[0060] In this embodiment, the oxygen ion gas is selected as O3.

[0061] In step c), the surface treatment gas comprises a fluorine-based surface treatment gas, and the fluorine-based surface treatment gas comprises one or a combination selected from HF, NF3 and F2 gases;

[0062] The etching gas includes one or a combination of trimethylaluminum, trimethylamine (TMA), dimethylacetamide (DMAC), tetrachloride, and also includes Sn(acac)2, Al(CH3)2Cl, SiCl4, TiCl4, BCl3 or WF6. Different etching gases can be used to etch different semiconductor materials.

[0063] The core material SiO2 particles in this embodiment can also be replaced by non-semiconductor metal oxides, or semiconductor nanoparticles with a diameter of 50-100 nm.

[0064] The quantum dots prepared by the above method of the present invention do not have the problem of agglomeration, so there is no need to coat the quantum dots with a protective layer. Therefore, there is no problem that the quantum dots are absorbed by adjacent quantum dots due to the thickness of the protective layer, thus avoiding the problem of low luminous efficiency of the prepared quantum dots. The diameter of the quantum dot composite microspheres in this embodiment is about 105nm.

[0065] Example 2

[0066] Referring to the preparation steps of Example 1, different semiconductor materials are selected to prepare quantum dot composite microspheres:

[0067] Replacing the source gas and reaction gas in step b) with other types in Table 1, depositing different types of quantum dot films, and then using atomic layer etching technology to etch the deposited different types of quantum dot films to less than 5 nm, has wide applicability.

[0068] In step b), the source gas and the reaction gas include at least one of an organic complex containing IIB subgroup elements and a halide and any one of a hydride and a single gas containing a VI main group element, which can react with each other to deposit II-VI semiconductors on the surface of the core material SiO2 particles. II-VI semiconductors include ZnO, ZnS, CdS, ZnSe, CdSe, HgSe, HgS, CdTe, ZnTe, HgTe, and CdSeTe.

[0069] In step b), the source gas and the reaction gas include at least one of organic complexes and halides containing group IIIA elements and any one of hydrides and organic complexing gases containing group V elements, which can react with each other to deposit group III-V semiconductors on the surface of the core material SiO2 particles. The group III-V semiconductors include GaN, InN, GaP, InP, and GaTe.

[0070] In step b), the source gas and the reaction gas include at least one of organic complexes and halides containing IVA main group elements and any one of hydrides and organic complexing gases containing VI main group elements, which can react with each other to deposit IV-VI group semiconductors on the surface of the core material SiO2 particles. The IV-VI group semiconductors include PbS, PbSe, PbTe, GeS, GeSe, and SnS2.

[0071] In step b), the source gas and the reaction gas include at least one of an organic complex containing a metal element and a halide and any one of a hydride containing a VI main group element and an organic complexing gas, which can react with each other to deposit a multinary metal chalcogenide semiconductor on the surface of the core material SiO2 particles. The multinary metal chalcogenide semiconductor includes: binary metal chalcogenides, ternary metal chalcogenides, and the ternary metal chalcogenides include CuInS.

[0072] The above II-VI semiconductors, III-V semiconductors, IV-VI semiconductors and multinary metal chalcogenide semiconductors are subjected to ALD deposition cycles using source gases and reaction gases in Table 1.

[0073] Table 1

[0074]

[0075] In the preparation process of the ternary quantum dots in Table 1, when atomic layer deposition is used to prepare the ternary quantum dot film, the source gas is replaced by a precursor of the multi-metal in Table 1, and the reaction gas is the reaction gas of the multi-metal in Table 1, and a binary metal chalcogenide is deposited, and then the atomic layer etching technology is used to etch the deposited quantum dot films of different types to less than 5nm, and then the source gas is replaced by another precursor of the multi-metal in Table 1, and the reaction gas is the reaction gas of the multi-metal in Table 1, and another binary metal chalcogenide is deposited, and then the atomic layer etching technology is used to etch the deposited quantum dot films of different types to less than 5nm, and then the source gas is replaced by another precursor of the multi-metal in Table 1, and the reaction gas is the reaction gas of the multi-metal in Table 1, and another binary metal chalcogenide is deposited, and then the atomic layer etching technology is used to etch the deposited quantum dot films of different types to less than 5nm, which has wide applicability.

[0076] Example 3

[0077] Referring to the steps of Example 1 or Example 2, quantum dots are prepared using semiconductor nanoparticles as cores:

[0078] If the core material in step a) is selected as semiconductor nanoparticles ZnS with a diameter of 50-100 nm, there is no need to implement step b), and the atomic layer etching technology of step c) is directly used to etch the semiconductor core material into quantum dots with a diameter not greater than 10 nm.

[0079] Specifically, after the SiO2 particles in steps a) and b) of Example 1 are replaced with ZnS quantum dot particles with a diameter of 50-100 nm, step c) is directly used to perform atomic layer etching on the ZnS quantum dot particles with a diameter of 50-100 nm to adjust the particle size, thereby achieving full coverage from red light to blue light.

[0080] Example 4

[0081] Referring to the preparation method of the semiconductor coating layer listed in Example 1, Example 2 or Example 3, the atomic layer deposition + atomic layer etching method of Example 1, Example 2 or Example 3 is repeated outside the core material to coat different quantum dot films layer by layer, and each layer of quantum dot film is no larger than 5 nm. The following quantum dots are prepared, and the photoluminescence properties of each quantum dot are tested, as shown in Table 2 below.

[0082] Table 2

[0083]

Claims

1. A method for preparing quantum dot composite microspheres by atomic layer deposition and atomic layer etching, characterized in that: The following steps are involved: S01. Using atomic layer deposition to coat the core material with a semiconductor film; S02. Etching the semiconductor film coated in step S01 to a thickness of no more than 5 nm by atomic layer etching; S03 repeats steps S01~S02, successively coating multiple layers of different types of semiconductor films on the outside of the core material; The core material is a non-semiconductor metal oxide, and the metal in the metal oxide includes silicon.

2. The method according to claim 1, characterized in that The core material is prepared by the following method: using atomic layer etching to etch the core material having a diameter of not less than 50 nm to a diameter of not more than 10 nm, wherein the core material is a semiconductor nanoparticle; The material of the semiconductor film is different from that of the core material.

3. The method according to claim 2, characterized in that The diameter of the core material is 50-100 nm.

4. The method according to any one of claims 1 to 3, characterized in that The atomic layer deposition method comprises: placing a material to be coated in a reaction chamber; providing a source gas and a reaction gas, and growing a semiconductor film on the material to be coated.

5. The method according to claim 4, characterized in that The semiconductor film includes II-VI semiconductors, III-V semiconductors, IV-VI semiconductors and multinary metal chalcogenides; The source gas and the reaction gas include at least one of an organic complex containing a IIB subgroup element and a halide, and any one of a hydride containing a VI main group element and a single gas that can react with each other to deposit a II-VI semiconductor on the surface of the material to be coated; The source gas and the reaction gas include at least one of an organic complex containing a IIIA subgroup element and a halide, and any one of a hydride containing a V main group element and an organic complex gas, which can react with each other to deposit a III-V semiconductor on the surface of the material to be coated; The source gas and the reaction gas include at least one of an organic complex containing an IVA main group element and a halide and any one of a hydride containing a VI main group element and an organic complex gas that can react with each other to deposit a IV-VI group semiconductor on the surface of the material to be coated; The source gas and the reaction gas include at least one of an organic complex containing metal elements and a halide, and any one of a hydride and an organic complex gas containing a VI main group element, which can react with each other to deposit a multinary metal chalcogenide semiconductor on the surface of the material to be coated. The multinary metal chalcogenide semiconductor includes: binary metal chalcogenides and ternary metal chalcogenides.

6. The method according to claim 5, characterized in that The thickness of the semiconductor film grown on the material to be coated is not less than 5nm.

7. The method according to any one of claims 1 to 3, characterized in that The atomic layer etching method comprises: exposing the semiconductor material to be etched to a surface treatment gas, wherein the surface treatment gas reacts with the surface of the semiconductor material to be etched to form a modified layer on the semiconductor material to be etched; The semiconductor material to be etched on which the modified layer is formed is exposed to an etching gas, and the etching gas reacts with the modified layer to remove the modified layer on the semiconductor material to be etched.

8. The method according to claim 7, characterized in that The surface treatment gas comprises a fluorine-based surface treatment gas, wherein the fluorine-based surface treatment gas comprises one or a combination selected from HF, NF3 and F2 gases; The etching gas includes one or a combination of trimethylaluminum, trimethylamine (TMA), dimethylacetamide (DMAC), tetrachloride, Sn(acac)2, Al(CH3)2Cl, SiCl4, TiCl4, BCl3, and WF6.

9. The method according to claim 8, characterized in that Before exposing the semiconductor material to be etched to the surface treatment gas, the method also includes the following steps: exposing the semiconductor material to be etched to the gas containing oxygen ions to modify the surface of the semiconductor material to form a surface passivation layer, wherein the gas containing oxygen ions includes one of N2O, O2, and O3.

10. A quantum dot composite microsphere, characterized in that: It includes a core material, and at least one semiconductor film made of a material different from the core material and sequentially coated outside the core material, the thickness of each semiconductor film layer is not more than 5nm, the core material is a non-semiconductor metal oxide, and the metal in the metal oxide includes silicon.

11. The quantum dot composite microsphere according to claim 10, characterized in that: The core material is semiconductor nanoparticles with a diameter no greater than 10 nm.

12. The quantum dot composite microsphere according to any one of claims 10 to 11, characterized in that: The semiconductor film includes II-VI semiconductors, III-V semiconductors, IV-VI semiconductors and multinary metal chalcogenide semiconductors. The multinary metal chalcogenide semiconductors include binary metal chalcogenides and ternary metal chalcogenides.

13. The quantum dot composite microsphere according to claim 12, characterized in that: The II-VI semiconductor includes ZnO, ZnS, CdS, ZnSe, CdSe, HgSe, HgS, CdTe, ZnTe, HgTe or CdSeTe.

14. The quantum dot composite microsphere according to claim 12, characterized in that: The III-V semiconductor includes GaN, InN, GaP, InP or GaTe.

15. The quantum dot composite microsphere according to claim 12, characterized in that: The IV-VI group semiconductor includes PbS, PbSe, PbTe, GeS, GeSe or SnS2.

16. The quantum dot composite microsphere according to claim 12, characterized in that: The multinary metal chalcogenide semiconductor includes: binary metal chalcogenides and ternary metal chalcogenides. The metal in the binary metal chalcogenide includes one of Cu, Mn, Ni, Ag, Eu, Co, Pb, Ge, Sn, Bi, and Sb. The metal in the ternary metal chalcogenide includes one or two of Cd, Cu, In, Zn, Fe, Sn, Ge, Ag, Co, Cr, Bi, and Sb.

Citation Information

Patent Citations

  • A neutral HgSe / CdSe / ZnSe double-shell quantum dot and its preparation method

    CN111662716B

  • Quantum dot composite microsphere, quantum dot composite microsphere membrane and preparation method of quantum dot composite microsphere membrane

    CN117467427A

  • Preparation method of red photonic crystal structure color thin film with photo-catalytic effect

    CN104817280A

  • Preparation method of ZnS-coated SiO2 surface nano-microsphere material

    CN113522185A